Case report: Uridine triacetate in the management of delayed onset 5-fluorouracil toxicity: A case report and review of literature - Jacob, Aasems; Sekkath Veedu, Janeesh; Selene, Insija; Raj, Rishi; Kannan, Lakshmi; Patel, Reema (Frontiers in Pharmacology, 2022)
5-fluorouracil (5FU) and capecitabine are fluoropyrimidine anti-neoplastic drugs commonly used in the treatment of different types of cancer. Hereditary dihydropyrimdine deaminase (DPD), thymidylate synthase mutations and drug overdose may lead to life-threatening toxicities. Uridine triacetate (UTA) is an emergency treatment for overdoses and early onset, severe or life-threatening toxicities from fluoropyrimidines. It is approved for use in adults and children within 96 hours of last fluoropyrimidine administration. We present the case of a 64-year-old male treated with 5-FU and oxaliplatin as adjuvant systemic therapy for stage IIIA rectal cancer who developed delayed central nervous system toxicity 18 days after initiating chemotherapy. He had rapidly worsening encephalopathy and ataxia. Laboratory workups, MRI brain and EEG were negative. He was started on UTA with concerns of 5-FU toxicity due to the life-threatening nature of his condition even beyond the recommended 96-hour time cut-off. He had rapid improvement in clinical status and resolution of encephalopathy. DPD deficiency testing later resulted as heterozygous for IVS14+1G>A allele indicating enzyme deficiency. This report demonstrates the importance of identifying delayed side effects with fluoropyrimidine therapy and potential treatment for reversing these effects. We also did an extensive literature review and obtained reports from the uridine triacetate clinical trials on patients receiving UTA after the 96-hour cut-off. Based on our experience and previous published reports, a patient developing life-threatening delayed 5-FU toxicity should also be considered for UTA on a case-by-case basis.